PENGARUH UKURAN PEMERINTAH DAERAH DAN KEKAYAAN PEMERINTAH DAERAH TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN (Studi pada Pemerintah Kabupaten/ Kota di Provinsi Jawa Tengah Periode 2015-2018) - Kurniawati, Devita; Sarwono, Aris Eddy; Sunarti, Sunarti (Universitas Slamet Riyadi, 2020)
This study aims to determine the effect of size of local government and wealth of local government on the level of disclosure of Local Government Finance Report. The sample in this study amounted to 140 District/ City of Local Government Finance Report in Central Java during the years 2015-2018, purposive sample method using path analysis. The analysis technique used is determine the estimation of panel data regression models, classic assumption test, multiple linear regression, t-test, f-test and test the coefficient of determination, with using E-views 10. The results showed that the variable of size of the local government have no effect on the level of disclosure of Local Government Finance Report, while the wealth of local government have effect level of disclosure of Local Government Finance Report.